Protection from gastrointestinal diseases with the use of probiotics - Marteau, Philippe R; Vrese, Michael de; Cellier, Christophe J; Schrezenmeir, Jürgen (The American journal of clinical nutrition, 2001)
Probiotics are nonpathogenic microorganisms that, when ingested, exert a positive influence on the health or physiology of the host. They can influence intestinal physiology either directly or indirectly through modulation of the endogenous ecosystem or immune system. The results that have been shown with a sufficient level of proof to enable probiotics to be used as treatments for gastrointestinal disturbances are 1) the good tolerance of yogurt compared with milk in subjects with primary or secondary lactose maldigestion, 2) the use of Saccharomyces boulardii and Enterococcus faecium SF 68 to prevent or shorten the duration of antibiotic-associated diarrhea, 3) the use of S. boulardii to prevent further recurrence of Clostridium difficile-associated diarrhea, and 4) the use of fermented milks containing Lactobacillus rhamnosus GG to shorten the duration of diarrhea in infants with rotavirus enteritis (and probably also in gastroenteritis of other causes). Effects that are otherwise suggested for diverse probiotics include alleviation of diarrhea of miscellaneous causes; prophylaxis of gastrointestinal infections, which includes traveler's diarrhea; and immunomodulation. Trials of gastrointestinal diseases that involve the ecosystem are currently being performed, eg, Helicobacter pylori infections, inflammatory bowel disease, and colon cancer.